Analysis of Income Inequality Between Rural And Urban Areas in West Java Province 2018 – 2022 - Astuti, Yuni; Arif, Muhammad (Majapahit Journal of Islamic Finance and Management, 2026)
This research is a quantitative study with an associative-causal (causal-comparative) approach, which aims to analyze the effect of income inequality on the Human Development Index (HDI), Labor Force Participation Rate (TPAK), and fiscal independence in West Java Province during the 2018–2022 period. The data used in this study are quantitative, with a focus on measuring income inequality, the Human Development Index (HDI), the Labor Force Participation Rate (TPAK), and fiscal independence. The type of data used is secondary data that describes the economic and social conditions of a region during a certain period. The data collection technique in this study uses the documentation method, considering that the research is quantitative with secondary data. Based on the goodness-of-fit model test in Cities and Regencies in West Java province, it is proven that the determinant coefficient (R2) value in Regencies is 27.39 percent while the determinant coefficient value (R2) value in Cities is 87.78 percent. Therefore, it can be concluded that the determinant coefficient value (R2) in cities is higher than the determinant coefficient value in regencies. Based on the t-test, it can be seen that the labor force participation rate in both cities and regencies has a negative and significant effect on income inequality. While the labor force participation rate itself has a significant impact on income inequality in regencies and cities, fiscal independence is not sufficient to influence income inequality in regencies and cities in West Java Province. The results of the goodness-of-fit model (F-test) for regencies and cities indicate that simultaneously, the human development index, labor force participation rate, and fiscal independence influence income inequality in regencies and cities in West Java Province.